Implementing 3600 Virtual Reality to Improve Students’ Conceptual Understandings of Structure and Function of Cell - Tantri, Ananda Kaliana; Fadilah, Rizka Elan; Bachtiar, Rayendra Wahyu (Experiment: Journal of Science Education, 2025)
Natural Science concepts, such as Structure and Function of cell, are often difficult for students to understand because of their microscopic characteristics and are not visible directly. This study aims to analyze the conceptual understanding of students before and after using Virtual Reality-based learning media and evaluate the effectiveness of the media in improving knowledge of Structure and Function of cell. The research was conducted at SMP 07 Ma'arif Perintis with the subject of class VIII students. The method used is qualitative research with exploratory study design. The results showed that after the use of virtual reality video, students had an increase in understanding of concepts. Interactive visualization presented through Virtual Reality technology helps students more easily uncover abstract concepts with concrete visual representations, thus supporting a deeper understanding of the structure and function of cell. Virtual reality-based learning media provides a more interesting learning experience and allows students to visualize the structure and function of cells clearly, thus helping to clarify concepts that are difficult to understand.